2015
DOI: 10.1007/s12079-015-0263-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased CCN2, substance P and tissue fibrosis are associated with sensorimotor declines in a rat model of repetitive overuse injury

Abstract: Key clinical features of cumulative trauma disorders include pain, muscle weakness, and tissue fibrosis, although the etiology is still under investigation. Here, we characterized the temporal pattern of altered sensorimotor behaviors and inflammatory and fibrogenic processes occurring in forearm muscles and serum of young adult, female rats performing an operant, high repetition high force (HRHF) reaching and grasping task for 6, 12, or 18 weeks. Palmar mechanical sensitivity, cold temperature avoidance and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
105
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(122 citation statements)
references
References 99 publications
(175 reference statements)
16
105
1
Order By: Relevance
“…A power analysis was performed using Statview using prior tissue TGF-β1 and grip strength data (Abdelmagid, Barr et al 2012, Fisher, Zhao et al 2015). We chose the most conservative sample size needed to detect differences with an alpha level of 0.05 and 80% power.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A power analysis was performed using Statview using prior tissue TGF-β1 and grip strength data (Abdelmagid, Barr et al 2012, Fisher, Zhao et al 2015). We chose the most conservative sample size needed to detect differences with an alpha level of 0.05 and 80% power.…”
Section: Methodsmentioning
confidence: 99%
“…We observed exposure-dependent declines in sensorimotor function after short-term performance of these tasks (≤3 months), with a high repetition high force (HRHF) task inducing the greatest dysfunction (Fedorczyk, Barr et al 2010, Barbe, Gallagher et al 2013, Fisher, Zhao et al 2015). We have shown that ibuprofen administered in weeks 5–6 of a 6-week HRHF task, or in weeks 5–12 of a 12-week HRHF task, attenuated inflammatory responses that drove tissue fibrosis (Abdelmagid, Barr et al 2012, Jain, Barr-Gillespie et al 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Evidence of tissue injury was paralleled by inlammatory responses, such as increased pro-inlammatory cytokines in lexor digitorum muscles and tendons [30][31][32]39], and increased macrophages in the median nerve at the level of the wrist (Figure 3A, B). Elevated levels of key pro-inlammatory cytokines, IL-1beta, and TNF-alpha were also observed in serum of rats that had performed a HRHF task for 12 weeks (12-week HRHF rats) ( Figure 3D, E).…”
Section: Ibuprofen Efectively Reduced Tissue Inlammation Induced By Tmentioning
confidence: 97%
“…Those suggested maximum limits are indicated in Table 1. 4. An operant rat model of WMSD Several animal models have been developed to study WMSDs and have shown that repetitive hand activities induce sensorimotor dysfunction [27][28][29][30][31][32][33]. A model developed in our laboratory is a unique operant rat model of voluntary reaching and grasping (Figure 1; [7,34]).…”
Section: Ibuprofenmentioning
confidence: 99%